Brief Emotional Intelligence Inventory for Senior Citizens (EQ-i-M20) - Pérez Fuentes, Mª; Gázquez Linares, José; Mercader Rubio, Isabel; Molero Jurado, Mª (Psicothema, 2014)
In recent years, diverse studies have been carried out revealing many benefits of high levels of Emotional Intelligence (EI) for the older population, affecting their physical and mental health, cognitive capacity, social functioning, and, ultimately, their well-being and quality of life. However, in Spain, there is no reliable and valid instrument for the assessment of EI. Hence, the goal of this work is the adaptation of the Emotional Intelligence Inventory: Young Version to the population of older university students. To achieve this goal, two studies were carried out (the first one of calibration, and the second of validation) with students from two Seniors Citizens' Universities (Almería and Oviedo). The results indicate that the instrument is reliable and structurally valid, although some doubts emerged about the appropriateness of one of the five factors (stress management) within this structure. The use of the EQ-i-M20 is recommended, although new studies are needed to shed light on the role of the factor stress management within the EI construct.